Whoever goes slowly (after eating) goes far - Betti, Federica; Dadda, Manuela; Ronchi, Barbara; Traina, Giovanni (Acta Biomedica Atenei Parmensis, 2022)
Food-dependent exercise-induced anaphylaxis (FDEIA) is an uncommon IgE-mediated hypersensitivity disease with limited prevalence data. Recently, reported cases of FDEIA have been increasing both in adults and children. FDEIA is the end condition depending on a summation process, and its pathogenetic mechanisms are not yet completely understood. Factors that add up their effects are food ingestion and physical effort and, in some cases, concomitant diseases, alcohol, drugs, emotional stress, menstruation, and particular weather conditions contribute to enhancing the reaction. Food-specific FDEIA (sFDEIA) implies the presence of an IgE-mediated sensitization to one or more foods, while in unspecific FDEIA (nsFDEIA), any food can induce anaphylaxis without sensitization.  Among causative foods, the most dominant trigger of FDEIA is wheat, in particular the allergen ω-5 gliadin (Tri a 19). Other common foods are seafood, seeds, grains, nuts, vegetables and fruit, cow’s milk, meat, and eggs.We present three cases of sFDEIA in children with clinical features and laboratory findings; the first was induced by a culprit food less frequently involved in sFDEIA than the others.